ZnO nanoparticle-induced oxidative stress triggers apoptosis by activating JNK signaling pathway in cultured primary astrocytes - Wang, Jieting; Deng, Xiaobei; Zhang, Fang; Chen, Deliang; Ding, Wenjun (Nanoscale research letters, 2014)
It has been documented in in vitro studies that zinc oxide nanoparticles (ZnO NPs) are capable of inducing oxidative stress, which plays a crucial role in ZnO NP-mediated apoptosis. However, the underlying molecular mechanism of apoptosis in neurocytes induced by ZnO NP exposure was not fully elucidated. In this study, we investigated the potential mechanisms of apoptosis provoked by ZnO NPs in cultured primary astrocytes by exploring the molecular signaling pathways triggered after ZnO NP exposure. ZnO NP exposure was found to reduce cell viability in MTT assays, increase lactate dehydrogenase (LDH) release, stimulate intracellular reactive oxygen species (ROS) generation, and elicit caspase-3 activation in a dose- and time-dependent manner. Apoptosis occurred after ZnO NP exposure as evidenced by nuclear condensation and poly(ADP-ribose) polymerase-1 (PARP) cleavage. A decrease in mitochondrial membrane potential (MMP) with a concomitant increase in the expression of Bax/Bcl-2 ratio suggested that the mitochondria also mediated the pathway involved in ZnO NP-induced apoptosis. In addition, exposure of the cultured cells to ZnO NPs led to phosphorylation of c-Jun N-terminal kinase (JNK), extracellular signal-related kinase (ERK), and p38 mitogen-activated protein kinase (p38 MAPK). Moreover, JNK inhibitor (SP600125) significantly reduced ZnO NP-induced cleaved PARP and cleaved caspase-3 expression, but not ERK inhibitor (U0126) or p38 MAPK inhibitor (SB203580), indicating that JNK signaling pathway is involved in ZnO NP-induced apoptosis in primary astrocytes.